Investigation on indirect solar dryer for drying sliced potatoes using phase change materials (PCM). (2021) - Vigneshkumar, N.; Venkatasudhahar, M.; Manoj Kumar, P.; Ramesh, A.; Subbiah, Ram; Michael Joseph Stalin, P.; Suresh, V.; Naresh Kumar, M.; Monith, S.; Manoj kumar, R.; Kriuthikeswaran, M.
Abstract: The solar dryers are playing a pivotal role in the food industries for preserving edible items such as grains, vegetables, fish, etc., through the removal of moisture content from them. They are having benefit over the open air drying by protecting the food items from dust, insects and other detrimental things. Further, they are attributed to save a greater amount of energy and protect the ecosphere from degradation. The indirect type solar dryers are primarily consisting of a solar collector and a space to place sliced potatoes. Their moisture removal rate is high and the quality of the end product would also be improved by them. In this present work, an indirect type single-pass forced convection solar dryer was fabricated and paraffin was integrated with solar collector as phase changing material (PCM) to improve the off-sunshine hour performance of the solar dryer. The process parameters such as, moisture removal rate, moisture ratio and the dryer inlet temperature were investigated for drying sliced potatoes in two cases, namely, solar dryer without PCM (Plain Dryer) and solar dryer with PCM (PCM Dryer). The mass flow rate of air was maintained as 0.065 kg/s and the dryer was operated from 10.00 a.m. to 7.00 p.m. The obtained results were compared and the influence of amalgamating PCM with the solar dryer was analyzed and presented. The results demonstrated that the presence of PCM within the solar collector enhanced the drying room temperature significantly, two more hours after solar period. In addition, the percentage weight of moisture removal from potato slices was enhanced by 5.1% per day with the aid of paraffin.